Wednesday
March 22, 2017

Post a New Question

Posted by on Thursday, October 28, 2010 at 11:30am.

3x2+x+1=0

  • college - , Thursday, October 28, 2010 at 11:41am

    since it's not factorable, we use quadratic formula:
    x = [-b +- sqrt(b^2 -4ac)]/(2a)
    where a=3, b=1, and c=1
    substituting:
    x = [-1 +- sqrt(1^2 - 4*3*1)]/(2*3)
    x = [-1 +- sqrt(-11)]/6
    thus
    x = [-1 + i*sqrt(11)]/6 ; and
    x = [-1 - i*sqrt(-11)]/6
    *note: i = sqrt(-1)

    hope this helps~

  • college-typo - , Thursday, October 28, 2010 at 11:44am

    oops, some typo:
    x = [-1 + i*sqrt(11)]/6 ; and
    x = [-1 - i*sqrt(11)]/6

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question